2013
DOI: 10.3386/w19079
|View full text |Cite
|
Sign up to set email alerts
|

Does High Home-Ownership Impair the Labor Market?

Abstract: We explore the hypothesis that high home-ownership damages the labor market. Our results are relevant to, and may be worrying for, a range of policy-makers and researchers. We find that rises in the homeownership rate in a U.S. state are a precursor to eventual sharp rises in unemployment in that state. The elasticity exceeds unity: a doubling of the rate of home-ownership in a U.S. state is followed in the long-run by more than a doubling of the later unemployment rate. What mechanism might explain this? We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 36 publications
0
78
0
1
Order By: Relevance
“…Since Oswald's (1996) influential paper documenting this relationship, several studies have either replicated Oswald's empirical analyses with other datasets or tested related theoretical hypotheses using micro-economic data. Several studies using regional or cross-country data lend some support to the claim that a higher regional home-ownership rate leads to a higher rate of unemployment (Blanchflower and Oswald, 2013;Coulson and Fisher, 2009;Costain and Reiter, 2008;Munch et al, 2006;Di Tella and MacCulloch, 2005;Green and Hendershott, 2001;Nickell, 1998). Oswald (1996) hypothesises that this is caused by lesser geographical mobility of home-owners relative to renters.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Since Oswald's (1996) influential paper documenting this relationship, several studies have either replicated Oswald's empirical analyses with other datasets or tested related theoretical hypotheses using micro-economic data. Several studies using regional or cross-country data lend some support to the claim that a higher regional home-ownership rate leads to a higher rate of unemployment (Blanchflower and Oswald, 2013;Coulson and Fisher, 2009;Costain and Reiter, 2008;Munch et al, 2006;Di Tella and MacCulloch, 2005;Green and Hendershott, 2001;Nickell, 1998). Oswald (1996) hypothesises that this is caused by lesser geographical mobility of home-owners relative to renters.…”
Section: Introductionmentioning
confidence: 96%
“…Oswald (1999) and Blanchflower and Oswald (2013) discuss various potential labour market effects of home-ownership, some of which involve external impacts. The externalities are related to labour immobility and not-in-my-backyard (NIMBY) behaviour.…”
Section: Instrumental Variables Analysesmentioning
confidence: 99%
“…If people lose their job and if owning a house limits their mobility and hence reduces their opportunities to find a new job, home-ownership even aggravates the poor economic situation of these individuals. In fact, a recent study by Blanchflower and Oswald (2013) has found evidence for such negative externalities resulting from lower levels of labor mobility, longer commuting times and fewer new businesses. Furthermore, during the recent economic crisis housing prices have fallen dramatically in the US, which may have led to a "lock in" effect due to financial constraints faced by those whose housing debt exceeds the market value of their homes, although a recent study by Valetta (2013) did not find evidence for this.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to Davidoff, we analyse occupational choice conditional on housing tenure. Our work also relates to the literature on the economic impact of homeownership -for example on unemployment (Oswald, 1996;Blanchflower and Oswald, 2013) or on business start-ups (Fairlie, 2010;Wang, 2012). However, our focus is on the role of financial leverage rather than homeownership per se.…”
Section: Introductionmentioning
confidence: 95%